2015
DOI: 10.12688/f1000research.6589.2
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Severe acute respiratory distress by tracheal obstruction due to a congenital thyroid teratoma.

Abstract: Congenital teratoma is a rare condition and is a germ cell tumor composed of elements from one or more of the embryonic germ layers and contain tissues usually foreign to the anatomic site of origin. We report a case of a neck tumor diagnosed during pregnancy, initially thought to be a goiter. After birth the neck mass kept growing until it compressed the trachea and produced respiratory failure. The infant had a difficult tracheal intubation because of the compressing mass. The staff decided to surgically rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…2 A less prevalent form of HAE with normal C1 inhibitor (HAE-nC1-INH) has the distinctive charac-teristic of showing normal complement levels and affects mainly women, while men are often asymptomatic carriers. 3 In the largest Portuguese cohort that included 126 patients, HAE-nC1-INH was diagnosed in five patients (4%). 4 The pathophysiology of HAE-nC1-INH is unknown, although evidence suggests the role of excess generation of bradykinin, causing vasodilation and vascular permeability.…”
Section: Protection Of Humans and Animalsmentioning
confidence: 96%
See 3 more Smart Citations
“…2 A less prevalent form of HAE with normal C1 inhibitor (HAE-nC1-INH) has the distinctive charac-teristic of showing normal complement levels and affects mainly women, while men are often asymptomatic carriers. 3 In the largest Portuguese cohort that included 126 patients, HAE-nC1-INH was diagnosed in five patients (4%). 4 The pathophysiology of HAE-nC1-INH is unknown, although evidence suggests the role of excess generation of bradykinin, causing vasodilation and vascular permeability.…”
Section: Protection Of Humans and Animalsmentioning
confidence: 96%
“…5 However, pregnancy has shown a variable course in intensity and frequency of the attacks, even in the same patient, suggesting that the hormonal changes are not the only influencing factors. 3 Mechanical trauma due to uterine growth and fetal movements have also been proposed as aggravating factors. 3 However, a recent study revealed that attacks were more common during the first trimester (41.7%).…”
Section: Protection Of Humans and Animalsmentioning
confidence: 99%
See 2 more Smart Citations